ANALISIS POTENSI KEBANGKRUTAN DENGAN MENGGUNAKAN METODE Z-SCORE - Zainul Arifin; Larosa Dhea Martha (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
The objective of this study is to analyze the potential for bankruptcy of four cigarette companies listed on the Indonesia Stock Exchange for the 2016-2018 period using the Altman Z-Score method. The data used in the research were secondary data sourced from the financial statements of four companies taken using the purposive sampling method. The results indicated that, in 2018, one company went bankrupt, i.e., PT Bentoel International Investama Tbk. Meanwhile, the other three companies, i.e., PT Gudang Garam Tbk, PT Hanjaya Mandala Sampoerna, and PT Wismilak Inti Makmur Tbk, were categorized in a healthy condition. These results can be used as an early warning for investors in making safe investment decisions. As for companies that are predicted to go bankrupt, they can immediately find the right solution to improve their performance. Keywords: bankcuptcy, company share, financial ratio, Z-score